“When a Woman Recites an Incantation, a Serpent Recites it”: Female magic and medicine in Caesarius of Arles (Eventum: A Journal of Medieval Arts & Rituals, 2024)
Caesarius of Arles was regarded by the ecclesiastical environment of his times as an authority concerning religious rules and the correct behaviour of Christians. He wrote more than 240 sermons that were diffused by an atelier of copyists in Arles as well as by himself. His sermons were extremely successful, influencing preachers all over Christendom. Among many other subjects, some of Caesarius’ sermons were concerned with what he regarded as paganism and unorthodox practices undertaken by Christians. Caesarius’ reproaches were generally addressed to both men and women indiscriminately, but some reprimands were made specifically towards his female audiences. This article will analyze the practices that were regarded by Caesarius as being performed exclusively by women, relating them to ecclesiastical legislation and other contemporary sources. It will investigate the nature of these practices and their relationship with women’s role in society and the need to seek alternative solutions to problems that were not contemplated by Christianity or contemporary medicine. The analysis undertaken will reveal women’s agency in shaping their own religious and healing practices, using creative ways to overcome their marginalized position.
Keywords: magic; female medicine and healthcare; female practitioners; lived religion